(untitled) (Interdisciplinary Studies Journal, 2024)
The article addresses alternatives for the decolonization of management models at Brazilian universities, considering traditional public options and new private, for-profit or non-profit options. In the context of Brazilian universities, the traditional public model involves higher education institutions financed by the State and focused on the public interest. These universities are generally supported by government resources and offer free or affordable education. However, this model can be criticized for being influenced by colonial structures that perpetuate inequalities and privileges. On the other hand, there is a growing presence of private universities in Brazil, some of which operate on a non-profit basis. These institutions depend on private resources, such as monthly fees and donations, to finance their activities. The emergence of these private universities can be seen as an alternative to the traditional public model, seeking greater autonomy and flexibility in academic management. The issue of decolonization refers to overcoming the influence of colonialism on higher education systems, which can perpetuate Eurocentric worldviews and power structures. The decolonization of academic management models seeks to promote a more inclusive and diverse approach, giving voice to different perspectives and valuing marginalized knowledge and cultures. Alternatives for the decolonization of academic management models include the implementation of affirmative action policies to increase the representation of historically excluded groups, the valorization of indigenous and Afro-descendant knowledge and practices, the inclusion of local and popular knowledge in curricula, the creation of spaces for dialogue and community participation, among other measures. In summary, the alternatives for decolonizing the management models of Brazilian universities involve rethinking both the traditional public model and the new private for-profit/non-profit model, aiming to promote higher education that is more inclusive, diverse and engaged with the needs and perspectives of society. Brazilian.